Analisis Yuridis Penguatan Peran Lembaga Budaya dalam Pengawasan dan Penegakan Hukum Berbasis Kearifan Lokal (Pusat Riset dan Inovasi Nasional, 2026)
This research explores the significant role of cultural institutions in overseeing and enforcing laws based on local wisdom in Indonesia, a nation characterized by its rich cultural diversity. The purpose of this study is to analyze how cultural institutions, particularly customary law bodies, can help integrate local traditions and values into the formal legal system, ensuring that laws are more reflective of and responsive to the diverse communities across the country. The study employs a normative approach with a prescriptive method to examine the challenges and opportunities of incorporating local wisdom into national law, particularly in the realm of legal oversight and dispute resolution. The research reveals that, despite constitutional recognition of customary law, its practical implementation within the national legal framework remains hindered by conflicts between customary norms and formal legal structures. Key findings suggest that strengthening the role of cultural institutions in legal processes can enhance both the legitimacy and effectiveness of the legal system, promoting social harmony and fostering justice that resonates with the local context. Ultimately, the study concludes that empowering cultural institutions is vital for creating a legal environment that respects and integrates local wisdom, which will contribute to a more inclusive, fair, and sustainable legal system in Indonesia.